A Case-Control Study Investigating Spectral Power in the Brain During an Affective Shifting Task: A Cognitive Performance in Adolescents with and without Type 2 Diabetes (CPAT2D) Study - Eaton, Amelia (Université d'Ottawa / University of Ottawa, 2024)
Paediatric cases of type 2 diabetes (T2D) are becoming more common as rates of obesity rise in tandem. Literature has suggested that T2D is associated with poorer cognitive performance and lower overall brain health compared to healthy controls. Performance differences across several cognitive domains have previously been investigated by looking at changes in spectral power using electroencephalography (EEG). The purpose of this study was to determine if adolescents with T2D have lower spectral power in the theta, alpha, and beta bands during a complex cognitive and motor task, compared to those without. This question was addressed using a case-control study, comparing 11 adolescents with T2D (cases) to 11 who are apparently healthy and 11 who are at-risk of T2D, for a total of 22 controls. Cognitive performance was measured using an affective shifting task in tandem with EEG. Results did not reveal any significant differences between groups, which suggests that the adolescent brain may be still producing brain waves at a comparable rate to adolescents without T2D. Further research is needed to better understand at what point spectral power differences appear.
Keywords: Type 2 diabetes; EEG; Spectral power